Germline-restricted chromosomes of the songbirds - P. M. Borodin (Вавиловский журнал генетики и селекции)
Germline-restricted chromosomes (GRCs) are present in the genomes of germline cells and absent from somatic cells. A GRC is found in all species of the songbirds (Passeri) and in none of the other bird orders studied to date. This indicates that GRC originated in the common ancestor of the songbirds. The germline-restricted chromosome is permanently absent from somatic cells of the songbird, while female germline cells usually contain two copies of GRC and male ones have one copy. In females, GRCs undergo synapsis and restricted recombination in their terminal regions during meiotic prophase. In males, it is almost always eliminated from spermatocytes. Thus, GRC is inherited almost exclusively through the maternal lineage. The germline-restricted chromosome is a necessary genomic element in the germline cells of songbirds. To date, the GRC genetic composition has been studied in four species only. Some GRC genes are actively expressed in female and male gonads, controlling the development of germline cells and synthesis of the proteins involved in the organization of meiotic chromosomes. Songbird species vary in GRC size and genetic composition. The GRC of each bird species consists of amplified and modified copies of genes from the basic genome of that species. The level of homology between GRCs of different species is relatively low, indicating a high rate of genetic evolution of this chromosome. Transmission through the maternal lineage and suppression of the recombination contribute significantly to the accelerated evolution of GRCs. One may suggest that the rapid coordinated evolution between the GRC genes and the genes of the basic genome in the songbirds might be responsible for the explosive speciation and adaptive radiation of this most species-rich and diverse infraorder of birds.